Multisystem inflammatory syndrome in children characterized by enhanced antigen-specific T-cell expression of cytokines and its reversal following recovery - Nathella Pavan Kumar; Kadar M. Abbas; Rachel M. Renji; Aishwarya Venkataraman; Arul Nancy; Poovazhagi Varadarjan; Elilarasi Selladurai; Thankgavelu Sangaralingam; Ramya Selvam; Akshith Thimmaiah; Suresh Natarajan; Ganesh Ramasamy; et al. (Frontiers in Pediatrics, 2023)
BackgroundMultisystem inflammatory syndrome (MIS) in children is considered to be a post-infectious complication of COVID-19. T-cell responses in children with this condition have not been well-studied.MethodsWe aimed to study the immune responses in children with MIS in comparison to children with acute COVID-19 and children with other infections. Whole blood was stimulated with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)–specific antigens and flow cytometry was performed to examine CD4+ and CD8+ T-cell responses.ResultsChildren with MIS had higher frequencies of CD4+ and CD8+ T cells expressing cytokines at baseline and upon SARS-CoV-2 antigen–specific stimulation in comparison to children with COVID-19 and/or other infections. Children with COVID-19 also exhibited higher frequencies of CD4+ and CD8+ T cells expressing cytokines at baseline and upon SARS-CoV-2 antigen–specific stimulation in comparison to children with other infections. At 6–9 months following treatment and recovery, this enhanced response against SARS-CoV-2 antigens was down modulated in children with MIS.ConclusionOur study, therefore, provides evidence of enhanced activation of CD4+ and CD8+ T-cell responses in children with MIS and reversal following recovery.